Current Concepts and Future Perspectives in Mastectomy: Minimally Invasive Approaches and Advances in Reconstruction Techniques - Graca, Zofia; Wołoszczuk, Tomasz; Skowronek, Aleksandra; Kołodziej, Jakub; Siudmak, Elżbieta; Jeziorna, Julia; Iwanicki, Adam; Sawina, Agnieszka; Skawińska, Aleksandra; Łabuś, Maciej (Journal of Education, Health and Sport, 2026)
Introduction and purpose: Breast cancer remains the most common malignancy among women worldwide and represents a major cause of cancer-related mortality. Advances in oncological management have led to the development of multidisciplinary treatment strategies that integrate surgery, systemic therapy, and radiotherapy. Contemporary breast surgery increasingly incorporates reconstructive procedures using implants or autologous tissue, often supported by minimally invasive and robotic-assisted techniques. The aim of this review is to present current concepts and future perspectives in mastectomy, with particular emphasis on minimally invasive approaches and modern reconstructive methods. State of Knowledge: Modern breast surgery favors breast-conserving procedures or mastectomy combined with immediate or delayed reconstruction. Both implant-based and autologous techniques demonstrate satisfactory oncological safety and favorable aesthetic outcomes. Additionally, the introduction of endoscopic and robotic-assisted approaches has enabled procedures through smaller incisions, reducing surgical trauma and potentially improving postoperative recovery and cosmetic results. Conclusions: Current approaches to mastectomy combine oncological effectiveness with increasing attention to aesthetic outcomes and patient quality of life. The ongoing development of minimally invasive techniques, advances in reconstructive surgery, and the emergence of robotic technologies offer promising prospects for further improvement in surgical precision and patient satisfaction. Nevertheless, additional long-term studies and broader clinical experience are required to confirm the safety and effectiveness of these innovative approaches.